Struktur Organisasi Sosial Masa Prasejarah Ditinjau dari Cara Hidup dan Sistem Penguburan - Ketut Wiradnyana (Berkala Arkeologi Sangkhakala, 2007)
AbstractNuclear family is the smallest social structure organization in general social habitat nowdays. The social structure organization which according to three factors : sex, age, and livelihood also has been indicated in mesolithic time, based on skeleton findings and buried arcaheological supplies in shells midden, NAD Province. After that time, the explanation of social organization/social structure would been more understood specially for the buried system.